Metal and metalloid bioaccumulation in three centipedes (Chilopoda) - Mitić, Bojan; Borković-Mitić, Slavica; Stojsavljević, Aleksandar; Stojanović, Dalibor; Pavlović, Slađan; Vasiljević, Ljubica; Ristić, Nataša (Archives of Biological Sciences, 2022)
Paper description: The use of centipedes as bioindicators of trace metal pollution was assessed. The concentrations of Mn, Co, Ni, Cu, Zn, As, Se, Rb, Sr, Cd, Tl, Pb and U in animals and soil were measured by inductively coupled plasma mass spectrometry (ICP-MS). Centipedes bioaccumulated Se (especially flavidus), Zn (C. flavidus and C. anomalans) and Cd (C. flavidus and E. transsylvanicus). This is the first report where distinct bioaccumulation profiles of metals were established in centipedes. Abstract: Three centipede species (Clinopodes flavidus, Cryptops anomalans and Eupolybothrus transsylvanicus) were used as bioindicators of trace metal and metalloid pollution in Belgrade, Serbia. The concentrations of 13 elements (the metals Mn, Co, Ni, Cu, Zn, Rb, Sr, Cd, Tl, Pb and U and metalloids As, Se) in whole animals and soil were measured by inductively coupled plasma mass spectrometry (ICP-MS). Differences in the concentrations of some elements in the analyzed species were observed, both in response to the sites and between species. In most cases, the trace element concentrations were higher in centipedes from a polluted site (an industrial area near a busy street with heavy traffic) but C. anomalans and E. transsylvanicus had higher Mn concentrations at an unpolluted site (a deciduous woodland on Mt. Avala). C. flavidus was a good bioindicator for detecting differences between Zn, Se and Cd. C. flavidus and C. anomalans were more efficient in accumulating Zn than E. transsylvanicus. It appears that C. anomalans poorly accumulated Cd, unlike C. flavidus and E. transsylvanicus, which accumulated Cd according to the high bioaccumulation factor (BAF) values. We conclude that the centipedes C. flavidus, C. anomalans and E. transsylvanicus can be used as suitable bioindicators of trace element exposure. Their ability to accumulate trace elements was different and depends on their physiology and lifestyle as well as the route of exposure.